AN EMPIRICAL VALIDATION OF THE METHODOLOGY FOR MEASURING SELF-PERCEIVED AGE IN THE MIDDLE EASTERN MARKET - Heiens, Richard; Pleshko, Larry (PEOPLE: International Journal of Social Sciences, 2017)
The authors present and validate a method for measuring cognitive age in the Middle Eastern market. The proposed cognitive age measure appears to show internal consistency, reliability, and correlation with actual chronological age. Specifically, cognitive age is only slightly lower on average than actual chronological age among Middle Eastern consumers, and these differences are much less pronounced than has been found in previous cross-cultural studies. The cognitive age measure also demonstrates predictive validity regarding consumption behavior in the retail coffee industry. The findings show that as both measures of age increase, buyers are satisfied with a greater percentage of retailers. Nevertheless, as both forms of age increase, consumers visit fewer coffee shops per year. Although they tend to make fewer visits, both cognitively and chronologically older consumers spend more money on each retail coffee shop visit. In addition, total coffee consumption increases with increased cognitive and chronological age, presumably driven by greater consumption in non-retail venues.